Development of augmented reality human skeleton to improve students’ cognitive learning outcomes on movement systems practice - Nahri, Mochammad Hilman Amirudin; Abidin, Zainul; Soepriyanto, Yerry (Journal of Research in Instructional, 2024)
The purpose of this study was to develop and reveal the effect of using Augmented Reality Human Skeleton in learning of human movement system on students' cognitive learning outcomes. This study uses the Multimedia-Based Instructional Design development model from Lee & Owens. The developed media was tested for validity. Cognitive ability was measured using a description test and a paired t test was carried out. Researchers validated the product through material experts and obtained a perfect score, with a score of 100% for content quality and objectives and learning quality, which was stated as Very valid. Media validation also showed very good results, with a score of 100% for suitability, attractiveness, and usefulness, and 95% for Simplicity. In addition, the practicality test of the media by students obtained a score of 96% for appearance, 97% for convenience, and 95% for ease of understanding the material, all of which were stated as practical. The results of the study showed a significant influence of the implementation of this media on students' cognitive learning outcomes. The use of Augmented Reality Human Skeleton showed a significant increase in students' cognitive (pretest = 61.1 and posttest 87.9). Thus, the application of Augmented Reality Human Skeleton in learning the human movement system is proven valid, practical, and able to improve students' cognitive learning outcomes.